Maria Y Marta a chamber opera - Villanueva, Alexander John L.; Baes, Jonas (Quezon City College of Music, University of the Philippines Diliman, 2019)
"The libretto written by Ms. Sofia Paderes is based from the Gospel of John chapter 11, which accounts the situation surrounding the death and resurrection of Lazarus, brother of Mary and Martha, and the relationship Jesus had with them. Jesus was a dear friend to Mary, Martha, and Lazarus. Upon the death of Lazarus in the village of Bethany, they sent word to Jesus about what happened, but Jesus arrived too late. Even though Mary and Martha believed that Jesus was the all-powerful Son of God, they cannot help but to be emotional about his timing, which according to them, was four days late. But upon seeing Lazarus buried in the tomb, Jesus could not help but be emotional himself (John 11:35) on the death of his friend. Urging Mary and Martha to believe, he showed them his glory of God by resurrecting Lazarus from the dead. This presents a discussion and the conceptual construction of the symbolic aspects of the chamber opera".
Thesis (M. Music--Composition) -- University of the Philippines Diliman
Keywords: Chamber music; Operas